The Identity Construction of Solo's Adolescent regarding 'Narimo Ing Pandum' - Rini Darmastuti; Berta Esti Ari Prasetya; T Arie Setyawan P (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
Indonesia is a country that is well-know of its diverse ethnicities, languages, and local wisdom. The nation's potential, however, has gradually been threatened by globalization. Globalization was deemed responsible for not only the socio-cultural and local wisdom crisis but also the spread of consumptive behavior in society, including among adolescents.